FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN MEMBAYAR PAJAK BAGI PELAKU USAHA KECIL MENENGAH (Students' Journal of Accounting and Banking, 2012)
The study aimed to determine the factors that influence compliance of taxpayers pay tax stamps individual who has the Small and Medium Enterprises that located in the region of West Semarang. That research used primer data was acquired by distributing the questionnaires. Questionnaires are distributed as many as 100 respondents, the distribution method using accidental sampling method.The test results show that understanding and awareness of tax payers, and a good perception on the effectiveness of the tax system positive significanty influenced the taxpayer compliance, but perception of good against the council tax did not influence the taxpayer compliance.Keywords: Compliance taxpayer, paying tax awareness, understanding of the regulation taxation, the perception of the service tax authorities, the perception of the effectiveness of the taxation system.